AQbD enabled optimization of RP-HPLC method for the estimation of pioglitazone and vildagliptin and its forced degradation studies - P V Devi Swapna; G. Saravanan (Creative Pharma Assent, 2026)
Background: Diabetes mellitus is a metabolic disorder that is managed with combination therapy. Pioglitazone improves insulin sensitivity by activating PPAR-γ, whereas vildagliptin increases incretin activity by inhibiting DPP-4. Their fixed-dose combination requires reliable analytical methods for quality control and stability assessment. This study aimed to develop a green, stability-indicating RP-HPLC method using the Analytical Quality by Design (AQbD) approach. Methodology: A systematic AQbD strategy employing Central Composite Design (CCD) with 13 experimental runs was used to optimize critical analytical parameters. Chromatographic separation was performed on an Agilent 1260 Infinity II HPLC system using a Phenomenex C18 column (150 × 4.6 mm, 5 µm). Detection was carried out at 220 nm with a flow rate of 0.8 mL/min. The method was validated in accordance with ICH guidelines, and greenness was evaluated using the AGREE, MoGAPI, and BAGI metrics. Results and Discussion: Vildagliptin and pioglitazone were well resolved with retention times of 2.21 min and 3.47 min, respectively. Validation results demonstrated excellent precision, accuracy, and reliability. The method exhibited acceptable greenness with a high BAGI score of 82.5, an AGREE score of 0.66, and a MoGAPI value of 74. Stress degradation studies confirmed its stability-indicating capability, with maximum degradation under alkaline and oxidative conditions, while acidic, thermal, and photolytic stresses showed minimal effects. Conclusion: The proposed AQbD-driven, eco-friendly RP-HPLC method is sensitive, stability-indicating, and regulatory-compliant, offering reduced analysis time, enhanced robustness, and improved environmental performance, making it a sustainable and efficient approach for routine estimation of pioglitazone and vildagliptin.